Management of Santri Development Through ISPA Organizational Activities at Pondok Modern Ummul Quro Al-Islami Leuwiliang Bogor - Ahmad Idhofi; Muhamad Dinil Anani (al-Afkar, Journal For Islamic Studies, 2024)
Santri Organization is an intra-Islamic boarding school organization. Similar to OSIS in public schools, but there are many differences. The santri organization in the pesantren has a role compared to the OSIS in the school. At the Modern Islamic Boarding School Ummul Quro Al-Islami all these activities are controlled by the administrators of the Men's Santri Association (ISPA). Through these activities, it is hoped that students can develop self-discipline, improve morals, and can enrich and broaden their knowledge and skills. The formulation of the problem in this research is how is the management of student development through ISPA organizational activities?How are the activities of the ISPA organization at the Modern Islamic Boarding School Ummul Quro Al-Isalmi? How is the management of student development through ISPA organizational activities? While the purpose of this study was to determine the meaning and application of the management of student development through the activities of the ISPA organization at the Modern Islamic Boarding School Ummul Quro Al-Islami Leuwiliang, Bogor. The type of research that the author uses in this research is descriptive qualitative which explains thoroughly and in depth the results of the research conducted. Data collection techniques were carried out by means of observation, interviews and documentation. The object of this research is the management of the ISPA organization. From the results of this study, it was found that the management of santri development through the activities of the ISPA organization at the Modern Islamic Boarding School Ummul Quro Al-Islami used good management in fostering students. It can be seen by the implementation of four management functions, namely, planning, organizing, implementing and directing and five methods of coaching, namely, exemplary, attention, advice, habituation and rewards or punishments. And the activities of the ISPA organization at the Modern Islamic Boarding School Ummul Quro Al-Islami are going well, judging from the work program they have implemented.